Teaching and Learning Strategies and Issues in Higher Education - Bullen, Mark; Gisbert Cervera, Mercè (Universitat Rovira i Virgili, 2015)
Many reports over the last few years have analysed the potential use of games, videogames, 3D environments and virtual reality for educational purposes. Numerous emerging technological devices have also appeared that will play important roles in the development of teaching and learning processes. In the context of these developments, learning rather than teaching becomes the main axis in the organisation of the educational process. This process has now gone beyond the analogue world and face-toface education to enter the digital world, where new learning environments are being produced with ever greater doses of realism. Teaching and Learning in Digital Worlds examines the teaching and learning process in 3D virtual environments from both the theoretical and practical points of view.